PERCEPTIONS AND MANIFESTATIONS OF DISCRIMINATION IN THE UNIVERSITY CONTEXT. A STARTING POINT FOR ITS ERADICATION - Jiménez Mata, Silvia (2020)
This article is based on an investigation carried out during the years of 2017 and 2019 at the National University of Costa Rica. The research aimed to identify the perceptions of the students concerning the forms of discrimination related to gender, ethnic-race, sexual orientation and disability in the university environment. Hence, a mixed research approach was used, through the application of a questionnaire to a probabilistic sample of students and through the conformation of focus groups, all of which evidenced a high degree of manifestations of discrimination.